Cervical spine radiculopathy epidemiology: A systematic review. (25th July 2020) - Mansfield, Michael; Smith, Toby; Spahr, Nicolas; Thacker, Mick
Abstract: Background and objective: Cervical spine radiculopathy (CSR) is a disabling condition that has significant negative impacts on a person's mental health, physical functioning and social participation. Research has reported variable CSR incidence and prevalence among different populations. To date, no systematic review has been completed investigating the prevalence or incidence of CSR; therefore, our objective was to determine the incidence and/or prevalence of CSR in adults. Design and method: A systematic review was conducted including searches of PubMed (MEDLINE), EMBASE and CINAHL from inception to February 25, 2020. Studies including data on incidence and/or prevalence of CSR were included. Methodological quality was assessed using a modified Hayden, Cote and Bombardier appraisal checklist. Data were analysed narratively. Results: Nine low‐ to high‐quality studies were included in the final review. Incidence ranged between 0.832 and 1.79 per 1, 000 person‐years from two high‐quality and one low‐quality study. Prevalence values ranged from 1.21 to 5.8 per 1, 000 from four medium‐ to high‐quality studies. Prevalence values of 1.14% [95% confidence interval (CI): 0.45–1.82] and 1.31% (95% CI: 0.66–1.96) for males and females, respectively, were reported from one medium‐quality study. One medium‐quality study reported an unadjusted prevalence value of 6.3% for males and females. Conclusions: This is the first systematic review investigating the epidemiology of CSR in an adult population. This review reports a variable incidence rate and prevalence of CSR among specific populations; however, this was based on nine studies. There is a priority to investigate CSR epidemiology across other populations globally and standardising CSR diagnostic criteria.